Mouse Y-linked Zfy1 and Zfy2 are expressed during the male-specific interphase between meiosis I and meiosis II and promote the 2nd meiotic division. - Nadège Vernet; Shantha K Mahadevaiah; Yasuhiro Yamauchi; Fanny Decarpentrie; Michael J Mitchell; Monika A Ward; Paul S Burgoyne (PLoS Genetics, 2014)
Mouse Zfy1 and Zfy2 encode zinc finger transcription factors that map to the short arm of the Y chromosome (Yp). They have previously been shown to promote meiotic quality control during pachytene (Zfy1 and Zfy2) and at the first meiotic metaphase (Zfy2). However, from these previous studies additional roles for genes encoded on Yp during meiotic progression were inferred. In order to identify these genes and investigate their function in later stages of meiosis, we created three models with diminishing Yp and Zfy gene complements (but lacking the Y-long-arm). Since the Y-long-arm mediates pairing and exchange with the X via their pseudoautosomal regions (PARs) we added a minute PAR-bearing X chromosome derivative to enable formation of a sex bivalent, thus avoiding Zfy2-mediated meiotic metaphase I (MI) checkpoint responses to the unpaired (univalent) X chromosome. Using these models we obtained definitive evidence that genetic information on Yp promotes meiosis II, and by transgene addition identified Zfy1 and Zfy2 as the genes responsible. Zfy2 was substantially more effective and proved to have a much more potent transactivation domain than Zfy1. We previously established that only Zfy2 is required for the robust apoptotic elimination of MI spermatocytes in response to a univalent X; the finding that both genes potentiate meiosis II led us to ask whether there was de novo Zfy1 and Zfy2 transcription in the interphase between meiosis I and meiosis II, and this proved to be the case. X-encoded Zfx was also expressed at this stage and Zfx over-expression also potentiated meiosis II. An interphase between the meiotic divisions is male-specific and we previously hypothesised that this allows meiosis II critical X and Y gene reactivation following sex chromosome silencing in meiotic prophase. The interphase transcription and meiosis II function of Zfx, Zfy1 and Zfy2 validate this hypothesis.